2016
DOI: 10.1111/jpi.12332
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin rescues zebrafish embryos from the parkinsonian phenotype restoring the parkin/PINK1/DJ‐1/MUL1 network

Abstract: Multiple studies reporting mitochondrial impairment in Parkinson's disease (PD) involve knockout or knockdown models to inhibit the expression of mitochondrial-related genes, including parkin, PINK1, and DJ-1 ones. Melatonin has significant neuroprotective properties, which have been related to its ability to boost mitochondrial bioenergetics. The meaning and molecular targets of melatonin in PD are yet unclear. Zebrafish are an outstanding model of PD because they are vertebrates, their dopaminergic system is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 77 publications
2
53
0
Order By: Relevance
“…Recent evidence has also suggested that abnormal function of DJ-1 plays a role in the pathogenesis of PD [4244]. In this study, we also examined the role of DJ-1 in neuroprotective effects of Sal.…”
Section: Discussionmentioning
confidence: 95%
“…Recent evidence has also suggested that abnormal function of DJ-1 plays a role in the pathogenesis of PD [4244]. In this study, we also examined the role of DJ-1 in neuroprotective effects of Sal.…”
Section: Discussionmentioning
confidence: 95%
“…In other words, as compared to other antioxidants, melatonin is more effective in preventing damage caused by oxidative stress. Capable of crossing cell membranes and of easily reaching all cell compartments, it is taken up by mitochondria and can maintain mitochondrial homeostasis in different experimental models [78,84,85,86,87]. Melatonin increases membrane fluidity, electron transfer chain (ETC) complex activity, ATP production, and mitochondrial membrane potential, while reducing oxidative stress and closing mitochondrial permeability transition pores (MPTPs) [88].…”
Section: Melatonin: a New Treatment For Mucositismentioning
confidence: 99%
“…The administration of MPTP/MPP + also leads to a reduction in the mRNA and expression of fibroblast growth factor 9 (FGF9), which participates in the proliferation, differentiation, and survival of the cell. The expression and function of parkin/PINK1/DJ-1/MUL1 loop, which plays an important role in maintaining mitochondrial homeostasis, are also altered by this toxin [150, 158]. All these changes were normalized by melatonin treatment [148, 150, 154, 158] (Table 2).…”
Section: Neuroprotective Potential Of Melatoninergic System In Parmentioning
confidence: 99%